2003
DOI: 10.1053/rmed.2003.1435
|View full text |Cite
|
Sign up to set email alerts
|

Oral gemifloxacin once daily for 5 days compared with sequential therapy with i.v. ceftriaxone/oral cefuroxime (maximum of 10 days) in the treatment of hospitalized patients with acute exacerbations of chronic bronchitis

Abstract: In a randomized, open-label, controlled, multicentre study, the clinical and bacteriological efficacy, safety and tolerability of oral gemifloxacin (320 mg once daily, 5 days) was compared with sequential intravenous (i.v.) ceftriaxone (1 g once daily, maximum 3 days) followed by oral cefuroxime axetil (500 mg twice daily, maximum 7 days) in adult hospitalized patients with acute exacerbations of chronic bronchitis (AECB) (n = 274). The clinical success rates at follow-up (21-28 days post-therapy) in the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 22 publications
2
38
0
3
Order By: Relevance
“…Others have also documented an association between fluoroquinolones and C. difficile diarrhea. [28][29][30] This trend, first noted in 2001, is of particular concern because the fluoroquinolone-resistant strains appear to be hypervirulent and have been associated with nosocomial epidemics. [31][32][33][34] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also documented an association between fluoroquinolones and C. difficile diarrhea. [28][29][30] This trend, first noted in 2001, is of particular concern because the fluoroquinolone-resistant strains appear to be hypervirulent and have been associated with nosocomial epidemics. [31][32][33][34] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, several trials to date support the efficacy of gemifloxacin in the treatment of lower respiratory tract infections [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Wilson and colleagues compared the activity of gemifloxacin with that of IV ceftriaxone/oral cefuroxime in the treatment of 271 hospitalized patients with AECB. 49 The clinical success rates at follow-up were 86.8% for gemifloxacin vs. 81.3% for ceftriaxone/cefuroxime in the entire study population (treatment difference = 5.5; 95% confidence interval [CI]: -3.9, 14.9). In the clinical intention-to-treat (ITT) population the clinical results were 82.6% vs. 72.1% (95% CI: 0.7, 20.4).…”
Section: Clinical Studiesmentioning
confidence: 94%
“…These clinical trials, although intended to show the noninferiority of gemifloxacin, identified some clinically significant differences between gemifloxacin and comparator drugs: decreased length of hospitalization versus ceftriaxone/cefuroxime; 49 shorter time to eradication of H. influenzae when compared with clarithromycin; 50 increased bacteriological success rate in AECB when compared to amoxicillin/clavulanate. 51 More importantly for our purposes of comparing gemifloxacin with other fluoroquinolones, gemifloxacin had a higher clinical success rate when compared to trovafloxacin, 52 and a higher rate of success versus levofloxacin at long-term follow-up 54 in two high quality trials (both trials get high scores on Jadad scale).…”
Section: Gemifloxacin In Aecb Dovepressmentioning
confidence: 99%